Validity and reliability of the malay version modified vertigo symptom scale (MVMVSS) - Zainun, Zuraida (Universiti Sains Malaysia, 2012)
Balance disordered is one of the common problems among elderly and clinically the subjective measure for this problem is important. There is one newly translated Malay version of Modified Vertigo symptom scale (MVMVSS) by Davies et a.I 1998. Validity and reliability test is essential before this MVMVSS can be used clinically especially in newly translated questionnaire. This cross sectional study involves translation (4 professionals), face validity (Professionals, students, patient and public (n= 10)) and reliability test (Normal and healthy subjects (n=80)). All subjects were asked to complete the MVMVVS once. However, for reliability test they were asked to complete Malay Version Vertigo Symptom Scale (MVVSS) and MVMVSS form twice. MVMVSS showed a good validity with 100% agreements in forward and backward translation. It also showed good face validity with good feedback about the number of questions, understanding and overall format. Higher reliability test showed for both questionnaires with Cronbach’s alpha 0.91 for MVVSS and 0.85 for MVMVSS. In conclusion, this study shows that MVMVSS is a good validity and reliability.